2019
DOI: 10.1016/j.omtn.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Gene Editing at Major CFTR Mutation Loci

Abstract: Cystic fibrosis (CF) is a lethal autosomal recessive disease caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. Nuclease-mediated precise gene editing (PGE) represents a promising therapy for CF, for which an efficient strategy that is free of viral vector, drug selection, and reporter enrichment (VDR free) is desirable. Here we compared different transfection methods (lipofectamine versus electroporation) and formats (plasmid DNA versus ribonucleoprotein) in delivering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 30 publications
2
55
1
4
Order By: Relevance
“…Currently, the research focuses on improving the CF gene therapy with the use of the CRISPR/Cas9 system. These efforts are focused on increasing the delivery efficiency of CRISPR/Cas9 elements to target locus and obtaining sustained expression of the CFTR transgene [19,20]. It was demonstrated that precise integration of the human CFTR gene at a porcine safe harbor locus through CRISPR/Cas9-induced HDR-mediated knock-in allowed the achievement of persistent in vitro expression of the transgene in transduced cells.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Currently, the research focuses on improving the CF gene therapy with the use of the CRISPR/Cas9 system. These efforts are focused on increasing the delivery efficiency of CRISPR/Cas9 elements to target locus and obtaining sustained expression of the CFTR transgene [19,20]. It was demonstrated that precise integration of the human CFTR gene at a porcine safe harbor locus through CRISPR/Cas9-induced HDR-mediated knock-in allowed the achievement of persistent in vitro expression of the transgene in transduced cells.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Genome editors present a new possibility for therapeutic treatment of CF, although the low efficacy with gene therapy delivery agents studied to date may also apply to the delivery of genome editors. Repair of CF mutations has been demonstrated with ZFNs and Cas9 in vitro as well as in patient induced pluripotent stem cells [133][134][135][136][137][138][139][140], although testing in animal models has not yet been performed. CF is an interesting and challenging disease as the CF transmembrane conductance regulator (CTFR) gene is very large and there are numerous mutations associated with the disease.…”
Section: Looking Forward: Upcoming Areas For Gene Editor Clinical Trialsmentioning
confidence: 99%
“…CF is an interesting and challenging disease as the CF transmembrane conductance regulator (CTFR) gene is very large and there are numerous mutations associated with the disease. Several gene editing strategies have been used to treat CF including Cas9 targeted removal of mutations that lead to nonfunctional protein splicing [135], ZFNs and Cas9 used to repair the F508 mutation [134,[137][138][139][140], ZFNs used for the targeted addition of exons 11-27 of the CTFR gene into exon 11 as a functional gene correction [136], and Cas9 utilized to add a functional copy of the CTFR gene into an AAVS1 safe site [133].…”
Section: Looking Forward: Upcoming Areas For Gene Editor Clinical Trialsmentioning
confidence: 99%
“…To list a few examples of preclinical advances in CRISPR therapy, multiple groups have been successful in treating hereditary tyrosinemia I, using Cas9, in disease models by correcting disease-causing FAH mutations [ 47 , 48 ] or knocking-out HPD [ 49 ]. Similarly, researchers applied Cas9 to effectively correct a disease causing mutation in CFTR to treat monogenic cystic fibrosis in patient-derived induced pluripotent stem cells [ 50 , 51 ]. Cas13 was developed as an antiviral to target the genomes of RNA viruses such as Influenza and SARS-CoV-2 in human lung epithelial cells to combat airway diseases [ 52 ].…”
Section: Potential and Application Of Crispr Therapeuticsmentioning
confidence: 99%